Identifikasi Tingkat Risiko Kecelakaan Kerja Menggunakan Metode HIRARC - Mohamad Nur Yorisyah; Andivas, Marulan; Kisanjani, Alex; Ismail Kurnia, Wahyu (Fakultas Teknik UMRI, 2025)
The rapidly growing manufacturing and service industries require various companies to improve operational efficiency, including in maintaining occupational safety and health (K3). CV. XYZ is a company that produces liquid organic fertilizer, granule biofertilizer, and vegetable pesticides. This research aims to identify potential hazards, analyze the level of risk of work accidents, and provide risk control recommendations using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. The results show that the potential risks vary from low to high levels. The two highest risks are electrical accidents during machine maintenance and injuries from falls during waste transfer. Control recommendations include the use of personal protective equipment (PPE), strict implementation of safety procedures, improvement of work facilities, and provision of assistive devices. This research provides important guidance for companies in effectively managing occupational accident risks and creating a safer work environment.